2020
DOI: 10.1177/0020720920981535
|View full text |Cite
|
Sign up to set email alerts
|

Open project-based learning for dynamic adaptability of IT education

Abstract: The pace of technological change is accelerating, the duration of the trends is becoming shorter and the number of technological alternatives to solve IT problems grows quickly. Keeping IT higher education course curricula up-to-date becomes more and more challenging. This paper presents an empirical study that aims to assess whether an open-statement and open-solution methodology in an IT-related project-based learning (PBL) course led to the adaptation of the skills learned by students to the trends of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A distinct design of project-based learning is to let students determine, or determine with the instructor, the objectives of the project and the technology to be used. One of the conclusions of this work is that project-based learning greatly enhances the link between school or university education and the professional world (Tous & Freitag, 2020). So, overcoming the problem of lack of skills, be it critical reasoning, creativity, collaboration, or communication, as 21st-century skills possessed by students in civics subjects, can be done by changing how the learning process encourages Peri Pirdaus / Project-Based Learning Model Increases Student Creativity and Learning Outcomes in Pancasila and Citizenship Education Learning creativity.…”
Section: Introductionmentioning
confidence: 92%
“…A distinct design of project-based learning is to let students determine, or determine with the instructor, the objectives of the project and the technology to be used. One of the conclusions of this work is that project-based learning greatly enhances the link between school or university education and the professional world (Tous & Freitag, 2020). So, overcoming the problem of lack of skills, be it critical reasoning, creativity, collaboration, or communication, as 21st-century skills possessed by students in civics subjects, can be done by changing how the learning process encourages Peri Pirdaus / Project-Based Learning Model Increases Student Creativity and Learning Outcomes in Pancasila and Citizenship Education Learning creativity.…”
Section: Introductionmentioning
confidence: 92%
“…In PBL, students are presented with opportunities to apply theoretical knowledge to real-world scenarios through industryrelevant case studies and hands-on projects [40,41]. This experiential learning approach enabled them to cultivate valuable competencies such as problem-solving skills, critical thinking abilities, and adaptability [42][43][44][45][46]-qualities highly sought after in the job market.…”
Section: Project-based Learningmentioning
confidence: 99%
“…Similarly, Sindre et al (2018), in a study of PBL in an introductory programming course, indicated that the implementation of PBL led to increased student motivation and improved programming skills. Tous and Freitag (2020) found that students who took a PBL-based computer science engineering course gained the skills to work with current technologies for immediate industrial applicability. Knowing the basics helped them adapt to rapid changes in technology.…”
Section: Introductionmentioning
confidence: 99%